2006
DOI: 10.1021/bi061058e
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin, Conformational States, and Calcium Signaling. A Single-Molecule Perspective

Abstract: Single-molecule fluorescence measurements can provide a new perspective on the conformations, dynamics, and interactions of proteins. Recent examples are described illustrating the application of single-molecule fluorescence spectroscopy to calcium signaling proteins with an emphasis on the new information available in single-molecule fluorescence burst measurements, resonance energy transfer, and polarization modulation methods. Calcium signaling pathways are crucial in many cellular processes. The calcium bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 126 publications
8
67
1
3
Order By: Relevance
“…5c). This is supported by several lines of evidence: NMR data indicate that the linker helix between the domains is flexible in the absence of peptide 75 ; X-ray diffraction has trapped both an extended structure (Protein Data Bank (PDB) identity 1CLL) 76 and a closed structure (PDB identity 1PRW) 77 ; and single-molecule FRET distributions show that a wide range of interdomain distances are sampled 78,79 . This flexibility of calmodulin on the microsecond-to-millisecond timescale allows the ligands to select their preferred conformation, explaining the specificity of calmodulin for so many targets.…”
Section: Fast Timescalesmentioning
confidence: 78%
See 1 more Smart Citation
“…5c). This is supported by several lines of evidence: NMR data indicate that the linker helix between the domains is flexible in the absence of peptide 75 ; X-ray diffraction has trapped both an extended structure (Protein Data Bank (PDB) identity 1CLL) 76 and a closed structure (PDB identity 1PRW) 77 ; and single-molecule FRET distributions show that a wide range of interdomain distances are sampled 78,79 . This flexibility of calmodulin on the microsecond-to-millisecond timescale allows the ligands to select their preferred conformation, explaining the specificity of calmodulin for so many targets.…”
Section: Fast Timescalesmentioning
confidence: 78%
“…Signal transduction, enzyme catalysis and protein-ligand interactions occur as a result of the binding of specific ligands to complementary pre-existing states of a protein and the consequent shifts in the equilibria 26,35,36,[75][76][77][78][79][90][91][92] (Fig. 1a).…”
Section: From Physics To Biology and Vice Versamentioning
confidence: 99%
“…[140][141][142][143][144][145] Numerous studies have shown that the apo form of CaM is much less stable than the Ca 2þ bound form. 141,144,145 Single molecule fluorescence resonance energy transfer (FRET) and fluorescence correlation spectroscopy (FCS) among many other methods have demonstrated decreased conformational dynamics and compaction of CaM upon Ca 2þ binding.…”
Section: Effects Of Ligands Osmolytes and Metal Ionsmentioning
confidence: 99%
“…Recent experimental data have shown the existence of fluctuations among multiple native conformations prior to the effector binding in several example allosteric proteins such as NtrC (nitrogen regulatory protein C) (7,8), CheY (9)(10)(11), calmodulin (12)(13)(14), and adenylate kinase (15)(16)(17), which has supported the view that the population-shift mechanism is not exceptional but may be ubiquitous in allosteric transitions (18)(19)(20)(21)(22)(23). There still remain, however, important questions to be elucidated: First, the actual mechanism in each allosteric protein may reside between two limits of population shift and induced fit, so that the relative importance of two mechanisms should be analyzed in each case (24).…”
mentioning
confidence: 99%